PREPARE CHILDREN IN SCHOOLS PEDAGOGICAL AND PSYCHOLOGICAL ISSUES - Turdiyeva Sohiba Rasuljon qizi; G'ulomjonov Odiljon Rahimjono'gli. (International Journal of Innovations in Engineering Research and Technology, 2021)
This article covers the pedagogical and psychological issues of preparing children for school education.